2010
DOI: 10.1002/syn.20836
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric assessment of acute and subacute ischemic neuronal damage: A small animal positron emission tomography study with rat photochemically induced thrombosis model

Abstract: We evaluated sequential changes in rat brain function up to 14 days after focal ischemic insult with a small animal positron emission tomography (PET). Unilateral focal ischemic cerebral damage was induced by left middle cerebral artery occlusion with a photochemically induced thrombosis (PIT) method. PET scans were conducted with [(11)C](R)-PK11195 ([(11)C](R)-PK) for peripheral benzodiazepine receptor (PBR), [(11)C]flumazenil ([(11)C]FMZ) for central benzodiazepine receptor (CBR), and [(18)F]fluoro-2-deoxy-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
53
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 38 publications
7
53
0
Order By: Relevance
“…Some reports showed the increase in 11 C-PK-11195 binding in peri-infarct regions, but not in infarct region, at Day-7 in rat ischemic model. 9,10 Another report reported no significant changes in 11 C-PK-11195 binding in either peri-infarct or infarct regions at Day-9, similarly increase in both regions Day-21 and later in baboon ischemic model, while 11 C-FMZ binding was significantly reduced from Day-2 and later. 29 Take together, the relationship between neuronal damage and inflammation might be altered depending on the species, models and timing after ischemic insult.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Some reports showed the increase in 11 C-PK-11195 binding in peri-infarct regions, but not in infarct region, at Day-7 in rat ischemic model. 9,10 Another report reported no significant changes in 11 C-PK-11195 binding in either peri-infarct or infarct regions at Day-9, similarly increase in both regions Day-21 and later in baboon ischemic model, while 11 C-FMZ binding was significantly reduced from Day-2 and later. 29 Take together, the relationship between neuronal damage and inflammation might be altered depending on the species, models and timing after ischemic insult.…”
Section: Discussionmentioning
confidence: 96%
“…39 We recently reported a relatively slow temporal change in the rat brain uptake of 11 C-FMZ after focal cerebral ischemia after Imaging impaired MC-I in ischemic monkey brain H Tsukada et al photochemically induced thrombosis. 9 In addition, 3 H-FMZ binding in vivo was relatively insensitive to cell death induced by sodium nitroprusside, a traditional NO donor compound. 40 These three previous studies and the present data suggest that FMZ binding to CBR might be considerably more stable against cell death, and providing more time to detect neuronal damage in the brain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this technique measures only the first part of glucose metabolism in the phosphorylation of glucose to glucose-6-phosphate by hexokinase (EC 2.7.1.1). Therefore, 18 F-FDG is taken up into not only normal tissues but also inflammatory regions observed in the subacute phase after transient focal ischemia in rodent models (11,12). Because recent reports indicated that several neurodegenerative disorders-schizophrenia, major depression, dementia (13,14), and autism (15)-induced neuroinflammation, 18 F-FDG may lead to underestimation of the neurodegenerative damage in these diseases.…”
mentioning
confidence: 99%